Association between living arrangements and health risk behaviors among the Hakka older adults in Fujian, China - Xiaojun Liu; Lingling Zhang; Huajing Chang; Mengshi Chen; Yimin Huang (BMC, 2023)
Abstract Background Behavioral lifestyles are important social determinants of health. The impact of changes in living arrangements on behavioral lifestyles is currently under-explored. This study aims to examine the association between living arrangements and health risk behaviors among the Hakka older adults. Methods Data were extracted from China's Health-Related Quality of Life Survey for Older Adults 2018. Living arrangements were divided into five categories: living alone, living with spouse only, living with child, mixed habitation, and others. Five health risk behaviors, including unhealthy dietary patterns, drinking, smoking, irregular sleep practices, and physical inactivity were measured. Logistic regression analysis was used to assess the association between living arrangements and specific health risk behaviors, and generalized linear models were established to test the association between living arrangements and the number of health risk behaviors. Results A total of 1,262 Hakka older adults were included in this study. Compared to those living alone, those living with spouse only were less likely to have unhealthy dietary patterns (OR = 0.45, P < 0.05) and drinking (OR = 0.50, P < 0.05), those living with the child were less likely to experience unhealthy dietary patterns (OR = 0.35, P < 0.001), drinking (OR = 0.32, P < 0.001), smoking (OR = 0.49, P < 0.05), and physical inactivity (OR = 0.13, P < 0.01). Moreover, those who were living with child (β = -0.78, P < 0.001) or mixed habitation (β = -0.33, P < 0.05) tended to engage in fewer health risk behaviors than those living alone. Conclusions This study suggests significant differences in health risk behaviors among the Hakka older adults with different living arrangements. Living with the child could reduce the occurrence of health risk behaviors in the Hakka older adults and thus maintain their health status.